SUN PROTECTION FACTOR (SPF) AND IRRITATION EVALUATION OF SUNSCREEN LOTION CONTAINING ETHANOLIC EXTRACT OF FIG FRUIT (Ficus racemosa L.) - Zilatul Ariani; Novia Suryani; Sulistiyana (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2026)
Excessive and prolonged exposure to sunlight may cause pigmentation, wrinkles, erythema, and an increased risk of skin cancer. Therefore, sunscreen products are needed to protect the skin from ultraviolet radiation. Fig fruit (Ficus racemosa L.) contains bioactive compounds such as flavonoids, steroids, saponins, and tannins that potentially act as natural sunscreen agents. This study aimed to evaluate the Sun Protection Factor (SPF) and irritation potential of sunscreen lotion containing ethanolic extract of Ficus racemosa L. fruit. The extract was obtained by maceration using 96% ethanol. SPF values were determined by UV-Vis spectrophotometry, and irritation testing was conducted using the Human 4-Hour Patch Test with 15 healthy female volunteers. The SPF values of the formulation containing 0 g (F0), 0.125 g (F1), 0.250 g (F2), 0.500 g (F3), and 1.000 g (F4) extract were 1.3473, 1.5970, 2.4371, 4.1191, and 4.3891, respectively. Based on SNI number 16-4399-1996, only F3 and F4 fulfilled the minimum SPF requirement of 4. No erythema or edema was observed in all formulations. These results indicate that higher extract concentration increased sunscreen activity, and F3 and F4 showed the highest SPF values with moderate sunscreen protection.